Analisis Kebutuhan Pelatihan dan Pengembangan Sumber Daya Manusia pada Lembaga Pendidikan - Sahrul Sahrul; Danial Rahman; Baharuddin Baharuddin (TADRIBUNA: Journal of Islamic Education Management, 2026)
This study analyzes the training and development needs of human resources in educational institutions through the method The research method used is library research through the collection of literature data from books, scientific journals with 25 relevant references. The research process takes place starting from topic determination, setting the focus, data collection, to the presentation of the report. The validity of the research results is tested through source triangulation to present an in-depth, objective, and informative analysis. The results of the study indicate that the success of human resource development in educational institutions is highly dependent on training needs analysis to align individual competencies with the target educational institution. The implication is, educational institution managers need to shift the paradigm by making training an investment strategy supported by valid competency mapping instruments and continuous post-training evaluation for the improvement of the overall quality of education.